A PROCESS FOR PREPARING SODIUM SILICATE FROM RICE HUSK ASH - RAUTARAY, Debabrata; LOLAGE, Mayura; ROKADE, Sunil; ANGAL, Ashwini; PARIDA, Prabhat (2018)
A process for preparing sodium silicate from rice husk ash is disclosed. Said process comprises fusing the rice husk ash with trona at an elevated temperature ranging between 1200-1500 °C for a time period ranging between 2-4 hours to obtain sodium silicate. L'invention concerne un procédé de préparation de silicate de sodium à partir de cendre de balles de riz. Ledit procédé comprend la fusion de cendre de balles de riz avec du trona à une température élevée comprise entre 1200 et 1500 °C pendant une durée comprise entre 2 et 4 heures pour obtenir du silicate de sodium.